Kepadatan dan Preferensi Habitat Kerang Pokea di Muara Sungai Laeya, Sulawesi Tenggara - Bahtiar Bahtiar; Ermayanti Ishak; Latifa Fekri (Jurnal Ilmu Pertanian Indonesia, 2023)
Freshwater clams or also known as pokes in tribal languange is clams to Sulawesi which posses high market value. However, their density and habitat preferences in Laeya River Estuary is currently unknown. This study aims to determine the density and habitat preferences of pokea clams in the Laeya River, Southeast Sulawesi. This research was conducted for 1 year from March 2016-February 2017. Pokea samples were taken every month in three stations using tangge (traditional fishing gear) with a total sample size of 2908 individuals. The density of pokea clam was analyzed using Mann Whitney test. Habitat preferences were analyzed by correspondence analysis using XLstat. The study showed that the density of pokea clams in 3 stations were similar. The clam density at stations I, II, and III were 85,47±66,44, 97,03± 81,70, and 59,84±82,31, respectively. The highest density was found during April-July 2016 with the peak density in May 2016 with a value of 268,78±29,23. The lowest density occurred during September 2016-February 2017. The lowest density was found in December 2016 with a value of 15,12±7,08. The density of pokea clams in the Laeya River was influenced by TDS. Pokea clams prefer habitats with deeper water and low brightness caused by organic matter and high TOM. Keywords: clam, Indonesia, pokea, preference, Sulawesi